2016
DOI: 10.1002/adhm.201600120
|View full text |Cite
|
Sign up to set email alerts
|

Functional Kidney Bioengineering with Pluripotent Stem‐Cell‐Derived Renal Progenitor Cells and Decellularized Kidney Scaffolds

Abstract: Recent advances in developmental biology and stem cell technology have led to the engineering of functional organs in a dish. However, the limited size of these organoids and absence of a large circulatory system poses limits to its clinical translation. To overcome these issues, decellularized whole kidney scaffolds with native microstructure and extracellular matrix (ECM) are employed for kidney bioengineering, using human-induced pluripotent-stem-cell-derived renal progenitor cells and endothelial cells. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…Nevertheless, currently recellularized renal and liver scaffolds can be used for the development of cellular assays for drug screening conditions. [245]…”
Section: Outlook and Perspectives Of Organ Decellularization/ Recellumentioning
confidence: 99%
“…Nevertheless, currently recellularized renal and liver scaffolds can be used for the development of cellular assays for drug screening conditions. [245]…”
Section: Outlook and Perspectives Of Organ Decellularization/ Recellumentioning
confidence: 99%
“…To avoid the in vivo differentiation process of PSCs, which could be partial, in 2016 Du et al injected into mouse decellularized kidney Pax2+ renal progenitor cells and endothelial cells derived from human iPSCs [82]. Following implantation for 12 weeks of the recellularized kidney into immunodeficient mice, the authors observed effective repopulation of the glomeruli only in the presence of both Pax2+ and endothelial cells concluding that endothelial cells are required for cellular assembly of the glomerular structures while they do not affect tubule repopulation [82]. In addition, the presence of endothelial cells positively influenced the filtration potential of the glomerular units measured by employing a bioreactor in vitro.…”
Section: Kidney-derived Scaffoldsmentioning
confidence: 99%
“…Results showed that only in the presence of endothelial cells were the glomeruli recellularized. Moreover, they showed in-vitro how endothelial cells improved glomerular barrier function (Du et al, 2016 ). Very recently Bombelli et al derived human nephrospheres, the spheres were shown to contain renal stem cell like cells.…”
Section: Kidneymentioning
confidence: 99%